2005
DOI: 10.1364/opex.13.000801
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear response of silicon photonic crystal micresonators excited via an integrated waveguide and fiber taper

Abstract: A technique is demonstrated which efficiently transfers light between a tapered standard single-mode optical fiber and a high-Q, ultra-small mode volume, silicon photonic crystal resonant cavity. Cavity mode quality factors of 4.7x10(4) are measured, and a total fiber-to-cavity coupling efficiency of 44% is demonstrated. Using this efficient cavity input and output channel, the steady-state nonlinear absorption and dispersion of the photonic crystal cavity is studied. Optical bistability is observed for fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
304
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(318 citation statements)
references
References 18 publications
10
304
2
2
Order By: Relevance
“…As an illustration, we consider a two-dimensional model of a photonic crystal consisting of a square lattice (lattice spacing a) of infinitely long dielectric rods (see Refs. [15,17,18] and also references [7][8][9][10][11][12][13][14][15][16] in Ref. [25]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an illustration, we consider a two-dimensional model of a photonic crystal consisting of a square lattice (lattice spacing a) of infinitely long dielectric rods (see Refs. [15,17,18] and also references [7][8][9][10][11][12][13][14][15][16] in Ref. [25]).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Noda's group have realized coupling of a PhC waveguide to a leaky resonator mode consisting of a defect pore of slightly increased radius [3][4][5][6]; Smith et al demonstrated coupling of a three-line PhC waveguide with a large-area hexagonal resonator [7]; Seassal et al have investigated the mutual coupling of a PhC waveguide with a rectangular microresonator [8]; Notomi et al [9] and Barclay et al [10] have observed all-optical bistability in direct-coupled PhC waveguideresonator systems.…”
Section: (C)mentioning
confidence: 99%
“…32,33 The present nanocavity thus ranks among those with the highest Q/V ratio ever reported. 1,6,11,15,17,[34][35][36] In the present work, we have additionally investigated an alternate optimal design 13 characterized by a smaller modal volume, that was obtained by introducing a stricter upper bound S 1x < 0.25a in the optimization procedure. The design has an ideal GMEcomputed Q-factor 1.05 Â 10 6 (FDTD: 1.0 Â 10 6 ) and a smaller modal volume V ¼ 0.25(k/n) 3 .…”
mentioning
confidence: 99%
“…As shown in panel (a) of the figure, at low power, a slight blue shift of the cavity mode is observed and attributed to free carrier dispersion. 6 Starting at P cavity ¼ 0.6 lW, heating due to nonlinear absorption, and optical-Kerr nonlinearity result in a redshift. At higher input powers, a drop in the spectral response on the red side of the resonance indicates the onset of optical bistability.…”
mentioning
confidence: 99%
“…Moreover, cavities with remarkable high quality factors (Q) [1,2] have been achieved recently, now permitting nanosecond photon lifetimes for enhanced light-matter interactions. The strong localization and long photon lifetimes in these high-Q/V m photonic crystal nanocavities point to enhanced nonlinear optical physics, such as Lorentzian-cavity-based bistability [3][4][5][6], Raman lasing [7,8] and cavity QED [9] in silicon photonics.…”
mentioning
confidence: 99%